Anomalous Origination of Right Coronary Artery from Left Sinus in Asymptomatic Young Male Presenting with Positive Ischemic Response on Treadmill Test - Budi Yuli Setianto; Anggoro Budi Hartopo; Putrika Prastuti Ratna Gharini; Nahar Taufiq (Case Reports in Cardiology)
Anomalous origination of coronary artery from the opposite sinus (ACAOS) is a rare coronary artery anomaly. Right ACAOS with interarterial course is a type of ACAOS, which conveys a high risk for myocardial ischemia or sudden death. We reported a case of right ACAOS with interarterial course in otherwise healthy young male. He was asymptomatic, until an obligatory medical check-up with treadmill test showed a sign of positive ischemic response. Further work-up revealed that he had right ACAOS with interarterial course. Watchful observation was applied to him, while strenuous physical activity and competitive sport were absolutely prohibited.